Making the connection: Value chains for transforming smallholder agriculture - Pye-Smith, Charlie (Technical Centre for Agricultural and Rural Cooperation, 2013)
The ‘Making the Connection’ conference on developing value chains for smallholder agriculture was the largest ever held on the topic. It focused on how to create efficient, market-led value chains that will ensure greater food security and improve the welfare of tens of millions of smallholder farmers. Participants discussed a wide range of policy issues, the most important of which are summarised here. These include ways of improving linkages between small farmers and buyers, the development of intra-regional trade, promoting an enabling environment and improving value chain finance.